Chorume: an experience in “Documentary Theater” (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This article discusses the trajectory of the Ortaet Theatre Company, the process of staging and researching language within the field of "Documentary Theatre," and some of the "stage documents" from the performance Chorume(2022), developed. Methodologically, I draw on "theatrical genetics," which aids in understanding and elaborating this journey, in which I am also a creative artist. The detailed analysis of the performance Chorume, created by the company in 2022, is based on the principle that the process and its outcome strengthened the political action of the Ortaet Company.
Keywords: Chorume; scene documents; Ortaet company; Iguatu dump